Field‐based individual plant phenotyping of herbaceous species by unmanned aerial vehicle. Issue 21 (19th October 2020) - Guo, Wei; Fukano, Yuya; Noshita, Koji; Ninomiya, Seishi
Abstract: Recent advances in Unmanned Aerial Vehicle (UAVs) and image processing have made high‐throughput field phenotyping possible at plot/canopy level in the mass grown experiment. Such techniques are now expected to be used for individual level phenotyping in the single grown experiment. We found two main challenges of phenotyping individual plants in the single grown experiment: plant segmentation from weedy backgrounds and the estimation of complex traits that are difficult to measure manually. In this study, we proposed a methodological framework for field‐based individual plant phenotyping by UAV. Two contributions, which are weed elimination for individual plant segmentation, and complex traits (volume and outline) extraction, have been developed. The framework demonstrated its utility in the phenotyping of Helianthus tuberosus (Jerusalem artichoke), an herbaceous perennial plant species. The proposed framework can be applied to either small and large scale phenotyping experiments. Abstract : A framework for field‐based individual plant phenotyping by UAV has been developed. Two main contributions, which are weed elimination for individual plant segmentation, and complex traits (volume and outline) extraction for Jerusalem artichoke, have been demonstrated in the paper.